2016
DOI: 10.1007/s12011-016-0913-y
|View full text |Cite
|
Sign up to set email alerts
|

Milk and Dairy Products Intake Is Associated with Low Levels of Lead (Pb) in Workers highly Exposed to the Metal

Abstract: Lead (Pb) is a toxic metal, frequently associated with occupational exposure, due to its widespread use in industry and several studies have shown high Pb levels in workers occupationally exposed to the metal. The aim of this study was to evaluate the influence of milk and dairy products (MDP) on Pb levels in blood (B-Pb), plasma (P-Pb), and urine (U-Pb), in workers from automotive battery industries in Brazil. The study included 237 male workers; information concerning diet and lifestyle were gathered through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…2018). Hence, high dairy intake, resulting in high Ca intake, might reduce Pb absorption and its related neurotoxic effects (Gomes et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2018). Hence, high dairy intake, resulting in high Ca intake, might reduce Pb absorption and its related neurotoxic effects (Gomes et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Chuang et al suggested milk protected workers against lead induced neuropathy ( 23 ). Gomes et al demonstrated intake milk and dairy products modulated level of lead in blood in workers highly exposed to the metal ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…9,29-31 Caregivers consistently reported that vouchers were used to purchase not only fresh fruits and vegetables but also food high in dietary iron and calcium, which are particularly important to lead-exposed children. 9,30,31…”
Section: Discussionmentioning
confidence: 99%
“…Although most farmers' market incentive programs restrict redemption to fresh produce, 11,16,21,28 the current program was intentionally designed to broaden access to foods high in nutrients believed to be protective during and after exposure to lead. 9,[29][30][31] Caregivers consistently reported that vouchers were used to purchase not only fresh fruits and vegetables but also food high in dietary iron and calcium, which are particularly important to lead-exposed children. 9,30,31 Caregivers appreciated the ease of voucher redemption as well as the positive reception from farmers' market vendors.…”
Section: Discussionmentioning
confidence: 99%